Strategies to cope with stress taking into consideration usage of psychoactive substances among group of nursing students - Szczyrba-Maroń, Barbara (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Studies and professional life are the potential source of stress, and the period of studies gives the possibility to learn methods how to cope with stress - either the constructive ones or the unconstructive ones. Usage and abusing of psychoactive substances take a special position among the methods of stress handling. The danger occurs when the person uses strategy of escaping-avoiding (such as psychoactive substances usage) so often that finally other methods of stress handling are pushed away. The problem occurs during studies when alcohol and other substances become helpers to cope with stress that students, later young doctors and nurses, experience every day. Aim of the study. The aim of researches presented was to describe stressful situations for first year nursing students of Medical Care Department of ŚUM in Katowice - licentiate studies, and recognition of methods how to cope with the problem. The questionnaire of WCQ Folkman, S. & Lazarus, R.S was used. Additionally usage of psychoactive substances was taken under consideration as a method to cope with stressful situations. Material and methods. 72 students of first year of nursing studies took part in researches. Researching tool was an inquiry of Agata Wons (Institution of Psychology of SUM in Katowice) and questionnaire WCQ Folkman, S. & Lazarus, R.S. Additionally usage of psychoactive substances was taken under consideration as a method to cope with stressful situations. Results and conclusions. The most frequently mentioned stressful situation for the questioned students were exams. The most frequently chosen method to cope with it was wishful thinking. Then self-blaming, fight and positive overvaluation and planning of the solution of the problem. 60% of researched students claimed not to use any of the substances to handle stress. Nobody declared usage of drugs as a method to cope stress. For 25% tablets are solution for stress, for 15% it is an alcohol. The conclusions seem to be alarming and bring up a reflection to create prophylactic programs describing how to manage with stress and usage of psychoactive substances. Nursing Topics 2010; 18 (4): 455-460